Pengaruh kinerja pegawai dan kualitas pelayanan publik terhadap kepuasan masyarakat dalam pembuatan Kartu Identitas Anak (KIA) di disdukcapil Kabupaten Tangerang - Aap Apriyani; Dede Saparudin; Unes Juhaeni (Universitas Tangerang Raya, 2023)
Human resources are the support for improving the quality of the agency for the better. This can be seen from the performance of each employee which is still less than optimal in completing the functions and tasks that have been determined by the regional government agency, this has an impact on the lack of employee performance. This study uses quantitative research with descriptive methods. The sampling technique in this research used a simple random sampling technique, the research used the Slovin formula. The number of samples used in this research was 100 samples. The sampling technique in this study used incidental sampling (non-probability sampling). Data analysis techniques in this study used validity test, reliability test, determinant test and hypothesis test. The variables used are employee performance (X1), public service quality (X2) and community satisfaction (Y). The resulting R Square value is 0.802, which is equal to 80.2%. So it can be concluded that variables X1 and The results of the T test of multiple regression analysis show that only the public service quality variable (X2) has a significant influence on public satisfaction (Y) while the employee performance variable (X1) has no significant effect on public satisfaction (Y).